2018
DOI: 10.1634/theoncologist.2017-0591
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Keytruda/Pembrolizumab Testing in Clinical Practice

Abstract: This Commentary addresses the FDA approval of pembrolizumab and the changes necessary in clinical practice to identify patients who would benefit from such treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…DNA MMR-deficient (dMMR) causes an increased rate of mismatch errors, which further triggers microsatellite instability (MSI) (Lynch et al, 2010). Notably, DNA MMR-deficient phenomenon is common in most types of tumors (Ratner and Lennerz, 2018). A previous study found that 42 out of 149 tumor specimens exhibited loss of MMR protein by IHC (Yamashita et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…DNA MMR-deficient (dMMR) causes an increased rate of mismatch errors, which further triggers microsatellite instability (MSI) (Lynch et al, 2010). Notably, DNA MMR-deficient phenomenon is common in most types of tumors (Ratner and Lennerz, 2018). A previous study found that 42 out of 149 tumor specimens exhibited loss of MMR protein by IHC (Yamashita et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…MSI is detected in about 15% of all colorectal cancers: 3% are associated with Lynch syndrome and about 12% are caused by sporadic, acquired hypermethylation of the promoter of the MLH1 gene, which occurs in tumors with the CpG island methylator phenotype [55]. MMR deficiency is also common in endometrial cancer, and other tumor types [56]. In a recent study, 42 of 149 tumor specimens exhibited loss of MMR protein by IHC.…”
Section: Standard Approved Biomarkers: Pd-l1 and Mmrmentioning
confidence: 99%
“…Studies suggest that IHC-based and MSI-based tests are both equally sensitive, with recommendations to use IHC-testing as a first line of screening because it is inexpensive and readily available [65]. In terms of dMMR testing, both PCR and IHC have ~ 90% sensitivity; combining both tests can increase sensitivity further [56].…”
Section: Standard Approved Biomarkers: Pd-l1 and Mmrmentioning
confidence: 99%
See 1 more Smart Citation
“…In August 2019 a further open label Phase I-II clinical trial investigating the efficacy and the safety of the combination of ataluren with pembrolizumab for the treatment of metastatic mismatch repair deficient and proficient colorectal adenocarcinoma and metastatic mismatch repair deficient endometrial carcinoma was sponsored by the University of Amsterdam (NCT04014530). Pembrolizumab (commercially available as Keytruda ® ) is a clinically approved humanized monoclonal antibody able to block the interaction between the programmed cell death protein (PD)-1 and its ligands which is currently used for the treatment of non-small-cell lung carcinoma (NSCLC) and other solid tumors [223]. Ataluren combination with Pembrolizumab was hypothesized because many deficient metastatic mismatch repair cancers often possessout-of-frame PTCs.…”
Section: Ataluren and Analoguesmentioning
confidence: 99%